2010
DOI: 10.1038/cdd.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Bid mediates the Atr-directed DNA damage response to replicative stress

Abstract: Pro-apoptotic Bid, a BH3-only Bcl-2 family member, is situated at the interface between the DNA damage response and apoptosis, with roles in death receptor-induced apoptosis as well as cell cycle checkpoints following DNA damage(Kamer et al., 2005; Yin et al., 1999; Zinkel et al., 2005). Here we demonstrate that Bid acts at the level of the sensor complex in the Atm and Rad3-related (Atr)-directed DNA damage response. Bid is found with Replication protein A (RPA) in nuclear foci and associates with the Atr/Atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 45 publications
2
46
0
Order By: Relevance
“…Thus, the phenotype in IR-stressed Bid À / À bone marrow differs from that observed following long-term replicative stress, consistent with our previous finding of a prominent role for Bid in the Atr-directed DDR. 19 We have previously demonstrated that Bid À / À cells display limited Atr function and increased sensitivity to replicative stress. 19,26 Furthermore, bone marrow of Bid À / À mice displays increased sensitivity to intraperitoneal injection of HU but not to IR, 19 and Bid À / À but not Bid þ / þ MPCs and LSK cells demonstrate increased Annexin V þ cells following HU (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the phenotype in IR-stressed Bid À / À bone marrow differs from that observed following long-term replicative stress, consistent with our previous finding of a prominent role for Bid in the Atr-directed DDR. 19 We have previously demonstrated that Bid À / À cells display limited Atr function and increased sensitivity to replicative stress. 19,26 Furthermore, bone marrow of Bid À / À mice displays increased sensitivity to intraperitoneal injection of HU but not to IR, 19 and Bid À / À but not Bid þ / þ MPCs and LSK cells demonstrate increased Annexin V þ cells following HU (Figures 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…6 To determine if the increased replating capacity of Bid À / À bone marrow was specific to treatment with HU, Bid þ / þ and Bid À / À mice were irradiated with low dose IR (2 Gy), chosen for a similar decrease in overall bone marrow cellularity in Bid þ / þ mice as observed with HU. 19 Bone marrow from 2 Gy IR-stressed Bid þ / þ and Bid À / À mice was harvested and cultured in methylcellulose. Both Bid þ / þ and Bid À / À bone marrow demonstrate modestly increased replating ability following 2 Gy relative to unstressed bone marrow.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations